Review of Screening and Monitoring Treatment of ADHD in Adults with Processing-Speed - Niels Peter Nielsen; Elisabeth H. Wiig (Highlights on Medicine and Medical Science Vol. 1, 2021)
The review objective was to examine characteristics and clinical uses of processing-speed measures in the management of adults with attention deficit/hyperactivity disorder. Normative and clinical data indicate no gender bias, high test-retest reliability, and acceptable levels of concurrent validity required for neuropsychological assessment. Recurring patterns in color-form naming and overhead values for adults with ADHD differ from those of healthy adults and adults with depression without ADHD or with dementia. The processing-speed profiles indicate average-normal response times for single-dimension colors and forms, longer-than-average response times for color-form combinations, and larger-than-average overhead values. Independent studies that monitored methylphenidate dose effects in medication-naïve and previously-medicated adults with ADHD and ADHD substance use disorder indicate statistical differences between color-form naming times and overhead measures at baseline without medication and at endpoint with stimulant medication. Results suggest that the measures may complement observational ratings of ADHD symptomatology in screening and monitoring stimulant-medication effects.